The Late Quaternary sediment successions of Llangorse Lake, south Wales. Issue 3 (June 2021) - Palmer, A.P.; Matthews, I.P.; MacLeod, A.; Abrook, A.; Akkerman, K.; Blockley, S.P.M.; Candy, I.; Francis, C.; Hoek, W.Z.; Kingston, F.; Maas, D.; El-Hady, S.R.; et al.
Abstract: The last British-Irish Ice Sheet (BIIS) created a landscape with many sedimentary basins that preserve archives of paleoenvironmental and paleoclimatic change during the Last Glacial-Interglacial Transition (LGIT; ~ 18-8 ka BP). The typical lithostratigraphic succession of these archives is composed of minerogenic/allogenic sediments formed during cold climatic conditions and organic-rich/authigenic sediments during warmer climates. This paper presents a multi-core lithostratigraphy compiled from the extant lake and surrounding basin at Llangorse Lake, south Wales, a basin lying within the southernmost limits of the last BIIS. This lake contains one of the longest continuous terrestrial sediment successions in the UK. Uncertainty previously existed concerning the presence and distribution of sediments at the site related to the Windermere Interstadial (~ 14.7 to ~ 12.9 ka BP) and Loch Lomond Stadial (~ 12.9 to 11.7 ka BP). A new borehole survey demonstrates that LGIT-age sediments are present at the site with nekron mud (gyttja), corresponding to the Lateglacial Interstadial, deposited in the deeper part of the lake waters and that these deposits are equivalent in age to marl deposits found at shallower depths at the margins of the basin. These deposits are associated with warmer conditions experienced during the Windermere Interstadial and Holocene, whilst minerogenic-rich sediments were deposited during the colder climatic conditions of the Dimlington Stadial and the Loch Lomond Stadial with rangefinder radiocarbon dates confirming this attribution. A model of lake level changes shows that drainage of the Dimlington Stadial glacial lake caused the largest fall, but there was also a further, smaller lake level fall at the end of the Windermere Interstadial and/or the start of the Loch Lomond Stadial, before the level rose in the early Holocene. The lithostratigraphic results presented here form the framework for further paleoenvironmental and paleoclimatic research at Llangorse Lake.